Penyuluhan Pencegahan Penularan HIV-AIDS dan IMS (Infeksi Menular Seksual) pada Remaja di SMA 1 Negeri Kuta Baro Aceh Besar Tahun 2022 - Alhuda, Alhuda; Vita Sari, Dian; Ahmady, Dedy; Suriani, Suriani; Masdiana, Erna (Nawadeepa: Jurnal Pengabdian Masyarakat, 2022)
A sexually transmitted disease is one of public health problem in the world, both in industrialized and developing countries. Also, the actual incidence and prevalence in various countries that are not well-known certainty. Some prevention methods to less the incidence of STIs and HIV/AIDS are by not having premarital sex among adolescents, to decrease the number of sexual partners (be faithful), using condoms while doing sexual, breaking the transmission of infection, increasing access and comprehensive prevention services. STI prevention services at health care centers provides condom for men and women, counseling for STI patients by giving education about preventing HIV infection to someone whom at risk of the disease, and tell to sexual partners. The objective of Adolescent Service to increase the understanding of the prevention of HIV-AIDS transmission and STIs (Sexually Transmitted Infections) as an effort to prevent infectious diseases in adolescents and can help government programs achieve the elimination of HIV-AIDS and infectious diseases. The method of this community service activity was carried out by socializing the delivery of material on preventing the transmission of HIV-AIDS and STIs (Sexually Transmitted Infections). The subjects in this service were students of SMA Negeri 1 Kuta Baro Aceh Besar, which attended by 30 students. The activity was carried out on October 6,2022 directly speech and demonstration method. The result of this counseling was found that almost half of the participants, as many as 12 people or 40% of the participants did not have a good understanding of Sexually Transmitted Infections. Yet after the counseling was held, there was a significant increase in the participants' understanding. This is evident from the posttest scores obtained by the participants. As many as 80% or 24 participants could answer the posttest questions correctly.